Friends’ Closeness and Intimacy From Adolescence to Adulthood: Art Captures Implicit Relational Representations in Joint Drawing: A Longitudinal Study - Snir, Sharon; Gavron, Tami; Maor, Yael; Haim, Naama; Sharabany, Ruth (Frontiers in Psychology, 2020)
This longitudinal study, employing a mixed-methods explanatory design, explored the power of art to express aspects of one’s inner world using the joint drawing technique, which allows for observation and treatment of implicit representations of relationships. At Time 1 (T1, 1977-78), 200 adolescents created a joint drawing with either a good friend or with a classmate who was not a friend, and filled out the Intimate Friendship Scale (IFS) in relation to their best friend. In 2014 (T2), 36 women and 21 men from the original cohort completed the IFS with regards to a good friend and with regards to their spouse. The drawings were analyzed qualitatively to define pictorial phenomena that may be indicative of closeness. The analysis was conducted in accordance with the phenomenological approach to art therapy and with the principles of thematic analysis. Fourteen pictorial phenomena were defined, and a scale was constructed to quantitively evaluate the extent to which each phenomenon was present in the joint drawing. This yielded a closeness score for each drawing. Quantitatively, no correlations were found between intimacy as measured by IFS at T1 and at T2. In contrast, there was a correlation between the degree of closeness in the joint drawing at T1, and the IFS score with the partner in T2, suggesting continuity over the 36-year time span. This correlation was likewise found when examined separately among participants who drew with a friend. The MANOVA results showed a marginally significant effect for the interaction between closeness in drawing and drawing with a friend/non-friend – on IFS. An ANOVA showed that the IFS regarding the participant’s best friend and their romantic partner at T2 was higher when the closeness in the drawing at T1 was higher. There was also a significant interaction between closeness in the drawings and the participant’s IFS score regarding their best friend at T1. The differences between the joint drawing with the close friend and the non-friend are discussed. These findings, from a span of over 36 years, thus contribute to the validity of the IFS and the joint drawing technique when assessing closeness and intimacy.